Leiomyoma with Lymphoid Infiltration: An Extremely Rare Histological Variant - Pujani, Mukta; Singh, Kanika; Chauhan, Varsha; Rana, Deepshikha; Arora, Sheetal; Agarwal, Charu (International Journal of Human and Health Sciences (IJHHS), 2019)
Background: Uterine leiomyoma with lymphoid infiltration is an extremely rare variant of leiomyoma. To the best of our knowledge, only 20 cases have been reported till date in the literature. Pathogenesis of this entity is not very clear. The various hypotheses which have been proposed to explain the etiopathogenesis include reactive alterations due to intrauterine pessaries, hormonal therapy or immune response dysregulation. Case report: We hereby report a case of a 44 year old female who presented with abnormal uterine bleeding. A small intramural leiomyoma was found which on pathological examination turned out to be leiomyoma with lymphoid infiltration. Conclusions: The importance of recognition this peculiar histological variant is to avoid possible misinterpretation as malignant lymphoma, inflammatory pseudotumororpyomyoma. In our case the lymphoid infiltration was reactive which was confirmed on immunohistochemistry International Journal of Human and Health Sciences Vol. 03 No. 03 July’19. Page: 162-164